Structure of the Yeast DEAD-Box Protein Mss116p Reveals Two Wedges that Crimp RNA - Campo, Mark Del (2009)
The yeast DEAD-box protein Mss116p is a general RNA chaperone that functions in mitochondrial group I and II intron splicing, translational activation, and RNA end processing. Here, we determined high-resolution X-ray crystal structures of Mss116p complexed with an RNA oligonucleotide and ATP analogs AMP-PNP, ADP-BeF(3)(−), or ADP-AlF(4)(−). The structures show the entire helicase core acting together with a functionally important C-terminal extension. In all structures, the helicase core is in a closed conformation with a wedge α-helix bending RNA 3′ of the central bound nucleotides, as in previous DEAD-box protein structures. Additionally, the C-terminal extension bends RNA 5′ of the central nucleotides, resulting in RNA crimping. Despite reported functional differences, we observe few structural changes in ternary complexes with different ATP analogs. The structures constrain models of DEAD-box protein function and reveal a new strand separation mechanism in which a protein uses two wedges to act as a molecular crimper.